Efektivitas Model Pembelajaran Panca Pramana dalam Meningkatkan Motivasi dan Hasil Belajar Pendidikan Agama Hindu dan Budi Pekerti Siswa SMP - I Ketut Agus Aryawan Adi Saputra; Made Redana; Ni Made Anggreni (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by findings that students’ learning motivation and learning outcomes in the subjects of Hindu Religious Education and Character Education at SMP TP 45 Denpasar were still suboptimal due to teaching that tended to be teacher-centered. This study aims to analyze the effectiveness of the Panca Pramana Learning Model. The novelty of this study lies in testing the model’s impact on learning motivation and learning outcomes. The study employed a quantitative approach using a True Experimental Design, specifically a Posttest-Only Control Group Design. The sample consisted of 25 students selected via simple random sampling, comprising 11 students in the experimental class and 14 students in the control class. Data were collected through a learning motivation questionnaire and an achievement test. Data analysis was conducted using descriptive statistics, the Independent Samples t-Test, and MANOVA. The results of the study indicate that the Panca Pramana Learning Model has a significant effect on students’ learning motivation (t = 5.168; p < 0.05), with an explanatory power of 53.7% (R² = 0.537). This model also had a significant effect on learning outcomes in the cognitive (R² = 0.510), affective (R² = 0.651), and psychomotor (R² = 0.265) domains, with all significance levels at p < 0.05. The MANOVA results indicate a significant simultaneous effect on students’ learning motivation and learning outcomes (Wilks’ Lambda = 0.187; p < 0.001). Thus, the Panca Pramana Learning Model effectively enhances students’ motivation and learning outcomes holistically.